Demokrasi di Tengah Pandemi COVID-19: Apa yang Didahulukan? Keselamatan atau Kepentingan - Alexsander Yandra; Adrian Faridhi; Khuriyatul Husna (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2022)
Indonesia as one of the countries that adhere to a democratic system continues to carry out direct regional head elections even though national health is a threat. The face-to-face campaign stage in the regional head election is one of the negative highlights of the Covid-19 incident because it is feared that it will cause a new cluster of Covid-19 cases. Therefore, this study will find and explore the problem of violating health protocols at the campaign stage carried out by candidates for regional heads. This study uses an approach with content analysis and phenomenology as methods. Data collection begins with the problem of violating health protocols at the campaign stage through news in 14 selected media. The results of the mapping in the form of trends and various polemics of violations are elaborated on cases of violations that occurred in the regions. The results of the study showed that violations of the health protocol were very high during the campaign period to violations of alleged criminal acts. Political contestation that occurred at the campaign stage during the pandemic did not become an obstacle for regional head candidates who took part in the election. So, it can be seen that the elections that took place during the pandemic were not in favor of the people because the political interests of regional head candidates were more important than public health as actors of democracy itself. Putting aside people's health is a bad record in the implementation of democracy.